ANALISIS PENGARUH NILAI HEDONIS DAN NILAI UTILITARIAN TERHADAP MINAT BELI DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (STUDI PADA PENGGUNA SITUS LAZADA DI KABUPATEN JEPARA) - Ardiansyah, Yusuf Figo; Rusdianto, Hutumo (Politeknik Negeri Lhokseumawe, 2025)
Abstract— This study aims to analyze the effect of hedonic value and utilitarian value on purchase intention with trust as an intervening variable among Lazada users in Jepara Regency. This study is quantitative in nature, with the population consisting of Lazada users in Jepara Regency who have never made a purchase. The sample was determined using purposive sampling with a total of 150 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) AMOS 24. The results of the study indicate that hedonistic values and utilitarian values have a positive and significant effect on purchase intention, hedonistic values and utilitarian values have a positive and significant effect on trust, trust does not affect purchase intention and is unable to mediate the relationship between hedonistic values and utilitarian values on purchase intention.Keywords— hedonic value, utilitarian value, trust, purchase intention